2019
DOI: 10.1186/s13065-019-0635-2
|View full text |Cite
|
Sign up to set email alerts
|

Two novel UPLC methods utilizing two different analytical columns and different detection approaches for the simultaneous analysis of velpatasvir and sofosbuvir: application to their co-formulated tablet

Abstract: In the present study two different RSLC columns, Acclaim RSLC 120 C18, 5.0 µm, 4.6 × 150 mm (column A) and Acclaim RSLC 120 C18, 2.2 µm, 2.1 × 100 mm (Column B) were utilized for the analysis of velpatasvir (VPS) in presence of sofosbuvir (SFV), where due to the encountered fluorescent properties of VPS fluorescent detection at 405 nm after excitation at 340 nm (Method 1) was used for its detection where the non-fluorescent SFV did not interfere. The same columns were further utilized for the simultaneous dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The drug is available in the form of 100 mg tablets. The IUPAC name of VEL is Methyl { The literature survey revealed that the methods reported [5][6][7] for the estimation of SOF and VEL individually or in their combined dosage forms by UV Spectroscopy [8][9][10] and RP-HPLC method [11][12][13][14] . The proposed method is highly recommended in routine analysis where method is more economical, rapid, precise, and accurate.…”
Section: Quick Response Codementioning
confidence: 99%
“…The drug is available in the form of 100 mg tablets. The IUPAC name of VEL is Methyl { The literature survey revealed that the methods reported [5][6][7] for the estimation of SOF and VEL individually or in their combined dosage forms by UV Spectroscopy [8][9][10] and RP-HPLC method [11][12][13][14] . The proposed method is highly recommended in routine analysis where method is more economical, rapid, precise, and accurate.…”
Section: Quick Response Codementioning
confidence: 99%
“…The official pharmacopeial monograph is also not available for the analysis of drug substance and pharmaceutical formulations. Very few analytical methods, focusing on simultaneous analysis of VEL and Sofosbuvir combined formulation, are reported in literature [ 13 , 14 , 15 , 16 , 17 , 18 ] Stability indicating methods for the analysis of VEL pure drug substance and degradation studies are also reported [ 19 , 20 , 21 , 22 , 23 ] but have limited information and discrepancies with published literature of FDA and MHRA [ 24 , 25 ]. As per MHRA public assessment report, VEL is photolabile, however it is reported stable in forced degradation studies published on UPLC [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, VLP determination in the presence of sofosbuvir was reported using a plethora of methods, including LC–MS/MS, , UPLC-ESCI MS/MS, HPLC–MS/MS, and HPTLC, in biological fluids and clinical studies. In addition, the determination of the two drugs in their pharmaceutical formula was addressed utilizing UPLC, spectrofluorimetry, UPLC/spectrofluorimetry, and spectrophotometry . However, the determination range is somewhat expensive and time-consuming.…”
Section: Introductionmentioning
confidence: 99%